(untitled) (Journal of Engineering, 2005)
This investigation presents coupled analyses of an carth-dam problem including all aspects of fluid structure interaction (class I coupling) and soil-pore fluid-structure interaction (class II coupling) under earthquake excitations using the finite element method and its comparison with the uncoupled one. New software for predicting and analyzing coupled behavour is established using the pressure formulation for modelling of the fluid and the u-p formulation for modelling of the soil-pore fluid The staggered partitioned solution technique for coupled field problems is implemented and used in the computer code. This scheme is incorporated in terms of a sequential execution for single-field analyzers. The bounding surface plasticity model is used as a constitutive relationship for modelling the clay core of a dam made up of Boston blue clay first and Baghdad brown silty clay later. The general theoretical framework of the model and its numerical implementation with emphasis on isotropic conesive soils are giveń. Also. the input material parameters are identified and the tests required for determining these parameters are clarified on Baghdad brown silty clay. Implicit Implicit Newmark’s numerical integration scheme with a correctorpredictor algorithm isemploved for time integraton of the en ahons omnn The resuits show ih u ine bounding surface plasticity model can give a logical impression for the behaviour of clayey soils under dynamie loads. Also, the earthquake design of structures generally and dams, in particular, must take into account various interactions between the foundation the structure and the water in the reservoir in addition to site effects. Amplifications due to stratification and dephasing (response lag) in the foundations of structures should also be considered.